Adaptive Learning Models for Gifted and Talented Students: Global Perspectives and Implementation Challenges - Pahrudin, Agus; Syafril, Syafrimen; Erlina, Nova; Saputri, Aprilis; Fitriani, Fitriani (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study examines adaptive learning models designed to optimize the potential of gifted and talented students from a global perspective. Using a systematic literature review (SLR) methodology, 21 articles from high-ranking journals (Q1 and Q2) and relevant academic books published between 2021 and 2024 were analyzed. The analysis identifies three primary models: the Enrichment Triad Model (ETM), the Differentiated Instruction Model (DIM), and the Autonomous Learner Model (ALM). Each model emphasizes critical elements such as deep learning experiences, curriculum flexibility, mentoring, and technology integration to foster creativity, critical thinking, and independent learning. The findings highlight the importance of adaptive educational paradigms that address not only the academic needs but also the social and emotional development of gifted students. The study also identifies significant challenges in implementing these models, particularly in developing countries like Indonesia, where resources and institutional support are often limited. The results provide practical insights into tailoring educational policies to meet the unique needs of gifted students, emphasizing the need for a balanced integration of global frameworks with local contexts. Future research is encouraged to explore adaptive learning implementations in diverse sociocultural settings to ensure equitable and inclusive education for gifted learners worldwide.